Ionic and conformational mobility in poly(vinylidene fluoride)/ionic liquid blends: Dielectric and electrical conductivity behavior. (9th May 2018) - Correia, D.M.; Sabater i Serra, R.; Gómez Tejedor, J.A.; de Zea Bermudez, V.; Andrio Balado, A.; Meseguer-Dueñas, J.M.; Gomez Ribelles, J.L.; Lanceros-Méndez, S.; Costa, C.M.
Abstract: The glass transition dynamics and the charge transport for blends composed of poly(vinylidene fluoride) (PVDF) and the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide, [Emim][TFSI] have been investigated as a function of different IL content (0, 10, 25 and 40 % wt) by differential scanning calorimetry (DSC), dynamic-mechanical analysis (DMA) and broadband dielectric relaxation spectroscopy (BDS) in wide frequency and temperature ranges (0.1 Hz–1 MHz and −120 to 150 °C, respectively). The inclusion of the IL in the polymer matrix affected the main relaxation process (β-relaxation) of the amorphous phase of the polymer matrix detected with all the techniques employed. It is demonstrated, that the chain segments of PVDF and the IL are mixed at the nanometer range. The blends were homogeneous regardless of the amount of IL and the glass transition temperature (Tg) shifted to lower temperatures as the IL content was increased. A good agreement between the Tg measured by BDS and DSC was observed for all PVDF/IL samples. The conductivity formalism revealed significant contributions of the IL concentration to the conductivity behavior of the blends in that is described by charge motion and electrode polarization effects. The activation energy of all the PVDF/IL samples, calculated by Dyre model, decreased with IL addition with respect to that of neat PVDF. Graphical abstract: Image 1 Highlights: Glass transition dynamics and charge transport of the PVDF/IL blends is studied. IL and PVDF are miscible the chain segments and the IL being mixed at the nanometer range. The inclusion of IL into PVDF affects the β-relaxation process. The effect of IL in the conductivity behavior is described in terms of charge motion and electrode polarization. The activation energy of the PVDF/IL samples decreases with IL addition.